Thin‐Film Deposition of an Organic Magnet Based on Vanadium Methyl Tricyanoethylenecarboxylate. (18th October 2014) - Lu, Yu; Harberts, Megan; Kao, Chi‐Yueh; Yu, Howard; Johnston‐Halperin, Ezekiel; Epstein, Arthur J.
<x xml:space="preserve">Abstract</x> The preparation and characterization of a new thin‐film organic‐based magnet V[MeTCEC]x (V = vanadium; MeTCEC = methyl tricaynoethylenecarboxylate) via low‐temperature chemical vapor deposition (50 °C) is reported. These thin films exhibit room‐temperature magnetic ordering and semiconducting behavior, demonstrating the ability of tuning their magnetic, and potentially spintronic, functionality via chemical modification of the organic ligand. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>